Removing Cobalt ions from Industrial Wastewater Using Chitosan - Kadhim, Hakim H.; Saleh, Khulood A. (Iraqi Journal of Science, 2022)
In batch experiments, a natural chitosan adsorbent was employed to extract cobalt ions from industrial wastewater under varied parameters of starting concentration, adsorbent weight, pH, and contact duration. The adsorbent was examined using FTIR, XRD, and AFM. For an initial cobalt ion concentration of 5x10-2 mol/l at pH 6, time 35 minutes, temperature 25 °C, and adsorbing dose 0.1 g, the results showed a maximum removal percentage of 99.0 percent. The Freundlich isotherm and the pseudo-second order kinetic model both suit the experimental data well. According to thermodynamic studies, the process was spontaneous and endothermic.